(untitled) (Research, Society and Development, 2024)
This research deals with the use of Jungian Art Therapy in the psychotherapy care of a child with a demand for aggression towards his mother, after the separation of his parents in compliance with a Judicial Protective Measure due to psychological domestic violence. The child was monitored at the Clínica Escola de Psicologia da Faculdade Mauricio de Nassau, Vitoria da Conquista, Bahia, Brazil, in the first half of 2023. This is a clinical case whose intervention was carried out through art therapy in the light of Jungian Analytical Psychology. The objective of this study was to analyze the effectiveness of art therapy as a child therapeutic tool in cases of children who feel insecure in talking about their emotions, preventing free association, transference and access from the subconscious to the conscious. Sessions were held with the child using art as a symbolic, non-verbal and metaphorical language through the Film Elements and the Archetypes identified by the child, in addition to other diverse materials for artistic production, enabling his behavioral perception, his emotions and feelings in relation to his family members and the divorce. The results showed that the child expressed himself through aggression because he felt guilty, punished and suffered parental alienation from his father in relation to his mother.